Cross laminated timber shear wall connections for seismic applications - Falk, Michael (Kansas State University, 2020)
This report gives a state-of-the-art summary of current cross-laminated timber (CLT) shear wall systems and connections for seismic applications. CLT panels are gaining popularity as a building material because of their biaxial strength and light weight. CLT panels can be used in building construction not only as floors, but also as shear walls. However, the behavior of CLT shear wall systems under seismic load has yet to be defined. CLT panels are nearly rigid under in-plane loading. While this can be beneficial, structural system qualities that are valuable in seismic loading such as ductility and energy dissipation are difficult to achieve by the panels themselves. Therefore, for the lateral force resisting system to perform as needed, ductility and energy dissipation must come from the connection systems. There is a distinction between a connection and a connection system. The performance of CLT shear walls depends on the behavior of many different connections. CLT shear walls can be categorized into conventional shear walls, and rocking walls. Conventional shear walls follow many of the practices established in light-frame wood shear walls with the use of hold-downs and brackets. Conventional shear walls typically have a base connection with (multi-panel walls) or without (single-panel walls) vertical joint(s). Selection of these two connections can have a noticeable effect on the shear wall behavior. Rocking shear walls allow panel rotation in order to redirect forces into structural fuses in the connection system. The structural fuses vary on the type of rocking wall. These include U-shaped flexural plates (UFPs), energy dissipators, slip-friction connections, and interpanel shear connections. Most of the systems covered in this report displayed favorable seismic performance. Case studies of full-scale buildings that were tested under seismic ground motions are presented. Studies indicated that CLT connections and shear walls have the capability to perform well under seismic loading.
Keywords: Cross laminated timber; Panel; Connections; Seismic; Rocking wall; Shear wall